Window Lighting sebagai Pembentuk Dimensi dan Karakter Objek Model dalam Fotografi Potret Hitam Putih - Fiandra, yosa; Sudaryat, Yayat (Program Studi Desain Interior Unikom, 2019)
ABSTRACT This article describes the role of window lighting in shaping the dimensions and character of object models, especially in black and white portrait photography. The method used in this study is descriptive analysis with a qualitative data approach. Data was collected from field observations and practices directly, with several model objects as samples from the study. Literature studies are also used to support and strengthen existing data. Analyzed data is verified with elements of embodiment of the form of the tangible aesthetic element. The results of this study indicate that window lighting can form the dimensions and character of objects in the black and white portrait model by emphasizing the visual elements in the object in the form, structure and expression that exist in the object model as a tangible form perceived by the eye. The contribution that can be given to this research is to broaden the knowledge of the basic lighting in photography. Key words : Light, Windows, Photography, Potrait, Human,